Phase I/II trial of a peptide-based COVID-19 T-cell activator in patients with B-cell deficiency - Jonas S. Heitmann; Claudia Tandler; Maddalena Marconato; Annika Nelde; Timorshah Habibzada; Susanne M. Rittig; Christian M. Tegeler; Yacine Maringer; Simon U. Jaeger; Monika Denk; Marion Richter; Melek T. Oezbek; et al. (Nature Communications, 2023)
Abstract T-cell immunity is central for control of COVID-19, particularly in patients incapable of mounting antibody responses. CoVac-1 is a peptide-based T-cell activator composed of SARS-CoV-2 epitopes with documented favorable safety profile and efficacy in terms of SARS-CoV-2-specific T-cell response. We here report a Phase I/II open-label trial (NCT04954469) in 54 patients with congenital or acquired B-cell deficiency receiving one subcutaneous CoVac-1 dose. Immunogenicity in terms of CoVac-1-induced T-cell responses and safety are the primary and secondary endpoints, respectively. No serious or grade 4 CoVac-1-related adverse events have been observed. Expected local granuloma formation has been observed in 94% of study subjects, whereas systemic reactogenicity has been mild or absent. SARS-CoV-2-specific T-cell responses have been induced in 86% of patients and are directed to multiple CoVac-1 peptides, not affected by any current Omicron variants and mediated by multifunctional T-helper 1 CD4+ T cells. CoVac-1-induced T-cell responses have exceeded those directed to the spike protein after mRNA-based vaccination of B-cell deficient patients and immunocompetent COVID-19 convalescents with and without seroconversion. Overall, our data show that CoVac-1 induces broad and potent T-cell responses in patients with B-cell/antibody deficiency with a favorable safety profile, which warrants advancement to pivotal Phase III safety and efficacy evaluation. ClinicalTrials.gov identifier NCT04954469.